The Relationship of Learning Motivation and Sentence Structure Mastery with Description Writing Ability - Sulasmi Sulasmi; Joko Sutrisno AB; Abdullah Abdullah (IJLHE: International Journal of Language, Humanities, and Education, 2018)
This study aims to describe the relationship between learning motivation and the ability to write descriptions, mastery of sentence structure and writing skills, and the relationship between learning motivation and mastery of sentence structure and ability to write descriptions. The research method used in this study is correlational, a type of research designed to determine or describe the relationship between existing variables. This study describes the relationship between learning motivation (X1) and mastery of sentence structure (X2) with the ability to write descriptions (Y). The findings showed that learning motivation and mastery of sentence structure are the essential variables that need attention to improve the ability to write reports of students of class VIII SMP, especially class VIII students of SMP Negeri 4 Way Tuba. in general. Motivation to learn and mastery of sentence structure is the essential part that students must master to improve their ability to write descriptions. The ability to write reports can increase if students have high mastery of sentence structure. Both aspects need to be enhanced by the teacher in line with efforts to improve the ability to write descriptions of students in class VIII SMP Negeri 4 Way Tuba.